Predicting the Unpredictable-A case Analysis of Kozhikode City. (2016) - Augustine, Anjith
Abstract: Cities have always been dynamic and transforming because of which the character of our urban spaces are also constantly changing. But this changing dynamics, is not fully understood by our current master planning process. The master planning being very linear in approach cannot accommodate these variations or dynamics and term them as chaotic. The paper tries to understand chaos as an underlying character of Indian Cities and to demonstrate a methodology of planning which can incorporate these changing dimensions. This in turn leads to more sustainable future cities.